IMPROVING THE STUDENTS’ SPEAKING SKILLS THROUGH 5E LEARNING CYCLE MODEL AT THE TENTH GRADE STUDENTS OF SMA NEGERI 3 PINRANG - Hasnidar, Hasnidar; Nurhamdah, Nurhamdah; Ismail, Ismail (Inspiring: English Education Journal, 2019)
This study was aimed to see the Improving Speaking Skill at SMA Negeri 3 Pinrang. The objective of this research is to get the empirical data of the differences between students? score of speaking test who were taught by using 5E learning cycle model and to know how 5E learning cycle model in teaching speaking. The research problem this study was ?can 5e learning cycle model improve the speaking skills?.The research method used in this research was pre-experimental with one group design. The data was collected through pretest and posttest. It aimed to know whether  5E  learning  cycle  model  in  teaching  speaking  can  improve  students? speaking skill.The population of this research consist of 280 students and the sample of the research X IS 3 that consist of 35 students.The finding revealed that 5E learning cycle model able to imropve students? speaking skills; it can be seen from the students score pre-test and post-test. the mean score of the pre-test score of the class was  1.48 and the mean score of the post-test score in class was 1.98. It means that teaching-learning by using 5E learning cycle model can be improved students? speaking skills.